Comparison of perioperative outcomes between standard laparoscopic and robot‐assisted approach in patients with rectosigmoid endometriosis. (10th June 2021) - Raimondo, Diego; Alboni, Carlo; Orsini, Benedetta; Aru, Anna Chiara; Farulla, Antonino; Maletta, Manuela; Arena, Alessandro; Del Forno, Simona; Sampogna, Veronica; Mastronardi, Manuela; Petrillo, Marco; Seracchioli, Renato
Abstract: Introduction: Robot‐assisted laparoscopic surgery (RALS) has gained widespread application in several surgical specialties. Previous studies on the feasibility and safety of RALS vs standard laparoscopy (S‐LPS) for rectosigmoid endometriosis are limited and reported conflicting data. This study aims to compare S‐LPS and RALS in patients with rectosigmoid endometriosis in terms of perioperative surgical and clinical data. Material and methods: This is a multicentric, observational, prospective cohort study including 44 patients affected by rectosigmoid endometriosis referred to two tertiary referral centers for endometriosis from September 2018 to September 2019. Patients were divided into two groups: 22 patients underwent S‐LPS, and 22 underwent RALS. Our primary outcome was to compare operative time (from skin incision to suture) between the two groups. Secondary outcomes included: operative room time (patient entry into operative room and patient out), estimated blood loss, laparotomic conversion rate, length of hospital stay, perioperative complications, and evaluation of endometriosis‐related symptoms at 12‐month follow up. Results: The two groups were comparable regarding preoperative and surgical data, except for higher rates of hysterectomies and bilateral uterosacral ligament removal procedures in the RALS group. Also after adjusting for these discrepancies, operative time was similar between S‐LPS and RALS. Operative room time was statistically longer in the RALS group compared with that of S‐LPS. No statistically significant difference was found concerning other study outcomes. Pain and bowel symptoms improved in both groups at 12‐month follow up. Conclusions: If performed by expert teams, RALS provides similar perioperative outcomes compared with S‐LPS in rectosigmoid endometriosis surgical treatment, except for longer operative room time.